Screening for Upper Cross Syndrome in Asymptomatic Individuals (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Upper cross syndrome has become prevalent in today’s population. This syndrome refers totightness of muscles such as pectoralis major, upper trapezius and levator scapulae and weakness of deepneck flexors, scalene, rombhoids, serratus anterior, middle and lower trapezius. Poor posture is associatedwith imbalance created in musculoskeletal system and common condition to be reported as upper crosssyndrome. It is commonly seen in people with forward head posture, desk job workers, dentist, beauticiansetc. The resulting clinical presentation is complaint of pain in neck and shoulder, cervicogenic headache,hunched upper-back and rounded shoulder. Children are not as proactive today and the rate of the Uppercross syndrome is on the rise. This deviated posture and sedentary lifestyle continues, where it progressesmore as the age progresses in adulthood. Aims and objectives: To screen, detect, early treat as well asprevent upper cross syndrome in young individuals. Materials and methods: Asymptomatic individualwith 20-40 years of age group will be explained about the procedure before commencement of the study.Posture will be screened using Kinect Azure and REEDCO Posture Assessment Scale will be used forevaluation. Assessment of muscle tightness and weakness will be evaluated using muscle length tests andmanual muscle testing.Results: The expected results would include details about prevalence of UCS in asymptomatic individual.The parameters of outcome measures will be analyzed using the statistical test namely students paired T-test.Conclusion: Based on previous data we assume it is essential to screen asymptomatic individual to looks forsigns of Upper Cross Syndrome for early detection, prevention and treatment.
Keywords: Upper Cross Syndrome, Kinect Auzure, Muscle Length Testing.